Acute administration of tramadol and tapentadol at effective analgesic and maximum tolerated doses causes hepato- and nephrotoxic effects in Wistar rats. (15th August 2017) - Barbosa, Joana; Faria, Juliana; Leal, Sandra; Afonso, Luís Pedro; Lobo, João; Queirós, Odília; Moreira, Roxana; Carvalho, Félix; Dinis-Oliveira, Ricardo Jorge
Abstract: Tramadol and tapentadol are two atypical synthetic opioid analgesics, with monoamine reuptake inhibition properties. Mainly aimed at the treatment of moderate to severe pain, these drugs are extensively prescribed for multiple clinical applications. Along with the increase in their use, there has been an increment in their abuse, and consequently in the reported number of adverse reactions and intoxications. However, little is known about their mechanisms of toxicity. In this study, we have analyzed the in vivo toxicological effects in liver and kidney resulting from an acute exposure of a rodent animal model to both opioids. Male Wistar rats were intraperitoneally administered with 10, 25 and 50 mg/kg tramadol and tapentadol, corresponding to a low, effective analgesic dose, an intermediate dose and the maximum recommended daily dose, respectively, for 24 h. Toxicological effects were assessed in terms of oxidative stress, biochemical and metabolic parameters and histopathology, using serum and urine samples, liver and kidney homogenates and tissue specimens. The acute exposure to tapentadol caused a dose-dependent increase in protein oxidation in liver and kidney. Additionally, exposure to both opioids led to hepatic commitment, as shown by increased serum lipid levels, decreased urea concentration, increased alanine aminotransferase and decreased butyrylcholinesterase activities. It also led to renal impairment, as reflected by proteinuria and decreased glomerular filtration rate. Histopathological findings included sinusoidal dilatation, microsteatosis, vacuolization, cell infiltrates and cell degeneration, indicating metabolic changes, inflammation and cell damage. In conclusion, a single effective analgesic dose or the maximum recommended daily dose of both opioids leads to hepatotoxicity and nephrotoxicity, with tapentadol inducing comparatively more toxicity. Whether these effects reflect risks during the therapeutic use or human overdoses requires focused attention by the medical community.